In vivo analysis of vascularization and biocompatibility of electrospun polycaprolactone fibre mats in the rat femur chamber. (29th May 2019) - Gniesmer, Sarah; Brehm, Ralph; Hoffmann, Andrea; de Cassan, Dominik; Menzel, Henning; Hoheisel, Anna‐Lena; Glasmacher, Birgit; Willbold, Elmar; Reifenrath, Janin; Wellmann, Mathias; Ludwig, Nils; Tavassol, Frank; et al.
Abstract: In orthopaedic medicine, connective tissues are often affected by traumatic or degenerative injuries, and surgical intervention is required. Rotator cuff tears are a common cause of shoulder pain and disability among adults. The development of graft materials for bridging the gap between tendon and bone after chronic rotator cuff tears is essentially required. The limiting factor for the clinical success of a tissue engineering construct is a fast and complete vascularization of the construct. Otherwise, immigrating cells are not able to survive for a longer period of time, resulting in the failure of the graft material. The femur chamber allows the observation of microhaemodynamic parameters inside implants located in close vicinity to the femur in repeated measurements in vivo. We compared a porous polymer patch (a commercially available porous polyurethane‐based scaffold from Biomerix™) with electrospun polycaprolactone (PCL) fibre mats and chitosan (CS)‐graft‐PCL modified electrospun PCL (CS‐g‐PCL) fibre mats in vivo. By means of intravital fluorescence microscopy, microhaemodynamic parameters were analysed repetitively over 20 days at intervals of 3 to 4 days. CS‐g‐PCL modified fibre mats showed a significantly increased vascularization at Day 10 compared with Day 6 and at Day 14 compared with the porous polymer patch and the unmodified PCL fibre mats at the same day. These results could be verified by histology. In conclusion, a clear improvement in terms of vascularization and biocompatibility is achieved by graft‐copolymer modification compared with the unmodified material.